Fabrication and optimization of N-Cu2O thin film using electrodeposition method for homojunction solar cell - Mohd Hanif, Asyikin Sasha (2018)
Cuprous oxide (Cu2O) is a promising semiconductor that has been getting attention as the alternative material for solar cell application. It is abundant, low cost and non-toxic to the environment. A homojunction Cu2O is said to provide high conversion efficiency for solar cell. However, as Cu2O is a natural p-type semiconductor, it is a challenge to make an n-type Cu2O. In this study, n-Cu2O was prepared by using electrochemical deposition. The structural, morphological, optical and electrical properties of the electrodeposited Cu2O were evaluated after optimizing the parameters for Cu2O fabrication. Structural characterization of the deposited thin film was also done via X-Ray Diffractions (XRD) to confirm the existence of Cu2O particles on fluorine-doped tin oxide (FTO) substrate and to determine the crystalline phases of Cu2O in the sample. The surface morphology of Cu2O thin films were characterized by Field Emission-Scanning Electron Microscopy (FE-SEM) in order to examine the changes in the surface morphology of the film as the parameter varied. Ultra violet-visible (UV-Vis) spectrophotometer was used to study the optical absorption of Cu2O and to determine the band gap of the deposited thin film with further calculation including the thickness values of the thin film measured by surface profiler. The resistivity and sheet resistance of Cu2O thin film were determined via four-point probe measurement test. Lastly, the deposited Cu2O thin film was confirmed as n-type by using the photoelectrochemical cell (PEC) test. The parameters for electrodeposition of Cu2O such as the deposition potential, pH solution, solution temperature, and deposition time were optimized at -0.10 V vs. Ag/AgCl, pH 6.5, 60 °C, and 60 minutes, respectively. The band gap obtained from UV-Vis spectrophotometer was 2.45 eV. The successful fabrication of n-Cu2O will open a new door of Cu2O-based homojunction development for thin film solar cell application.